(untitled) (Marketing Journal, 2025)
This article discusses the use of forecasting methods in the management of corporate cash flows and their significance in ensuring the financial stability of an enterprise. In particular, cash flow forecasting helps prevent liquidity shortages, facilitates the coordination of relationships with debtors and creditors, and supports the effective management of working capital. Furthermore, the regular application of forecasting techniques enhances financial discipline within the enterprise, strengthens interna l control mechanisms, improves operational efficiency, and contributes to the overall stability of the financial system. 264